2023
DOI: 10.3390/ma16114152
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Gas Release of 3D-Printed Furan Resin Sand Core during the Casting Process

Abstract: In sand casting, gas porosity is a common defect that can result in decreased strength, leakage, rough surfaces, or other problems. Although the forming mechanism is very complicated, gas release from sand cores is often a significant contributor to the formation of gas porosity defects. Therefore, studying the gas release behavior of sand cores is crucial to solving this problem. Current research on the gas release behavior of sand cores mainly focuses on parameters such as gas permeability and gas generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
1
0
Order By: Relevance
“…A good gas permeability reduces the metal filling resistance and can reduce the porosity defects on the surface, thus improving the quality of the castings. Wang et al [ 18 ] compared the exhaust speed of blind and hollow sand cores and found that the peak speed of the former was 1.10 m/s, which is lower than that of the latter, 1.89 m/s.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A good gas permeability reduces the metal filling resistance and can reduce the porosity defects on the surface, thus improving the quality of the castings. Wang et al [ 18 ] compared the exhaust speed of blind and hollow sand cores and found that the peak speed of the former was 1.10 m/s, which is lower than that of the latter, 1.89 m/s.…”
Section: Introductionmentioning
confidence: 99%
“…A good gas permeability reduces the metal filling resistance and can reduce the porosity defects on the surface, thus improving the quality of the castings. Wang et al [18] compared the exhaust speed of blind and hollow sand cores and found that the peak speed of the former was 1.10 m/s, which is lower than that of the latter, 1.89 m/s. Moreover, scholars have recently initiated studies on hollow sand molds, investigating the correlation between hollow structures and the performance of 3D-printed sand molds.…”
Section: Introductionmentioning
confidence: 99%